Analisis SWOT (Strenghts, Weaknesesses, Opportunity, Threats) Jasa Kelola Media Sosial KRUV - Rheiza Marell Anugerah; Moh. Farid Hidayat; Anggita Dana Salsa Bila; Bobby Dewantoro; Talita Karisma Syaharani (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This research aims to explore the application of SWOT analysis as an effort to enhance competitiveness and overcome challenges in managing the KRUV social media service. The research method applied is a quantitative descriptive approach. The SWOT analysis approach includes descriptive methods, SWOT matrix, and SWOT diagram analysis. Data collection is carried out through interviews, questionnaires, and literature reviews. The research findings indicate that further evaluation is needed for the SWOT analysis strategy to improve competitiveness, thereby strengthening the performance of the KRUV Social Media Management Service, both internally and externally, in expanding its business.